Can ACGME Milestones predict surgical specialty board passage: an example in Obstetrics and Gynecology - Sarah Ottum; Conrad Chao; Sejal Tamakuwala; Joshua Dean; Adib Shafi; Katherine Jennifer Kramer; Satinder Kaur; Maurice-Andre Recanati (IMR Press, 2021)
Background: Multiple tools including Accreditation Council for Graduate Medical Education (ACGME) standardized milestones can be utilized to assess trainee and residency program performance. However, little is known regarding the objective validation of these tools in predicting written board passage. Methods: In this retrospective study, data was gathered on n = 45 Wayne State University Obstetrics and Gynecology program graduates over the five-year period ending July 2018. United States Medical Licensing Examination (USMLE) scores, Council on Resident Education in Obstetrics and Gynecology (CREOG) in-training scores and ACGME milestones were used to predict American Board of Obstetrics and Gynecology (ABOG) board passage success on first attempt. Significance was set at p < 0.05. Results: Written board passage was associated with average CREOGs (p = 0.01) and milestones (p = 0.008) while USMLE1 was not significantly associated (p = 0.055). USMLE1 <217 (Positive predictive value (PPV) = 96%). CREOGs <197 (PPV = 100%) and milestones <3.25 (PPV = 100%), particularly practice-based learning and systems-based practice milestones were most strongly correlated with board failure. Using a combination of these two milestones, it is possible to correctly predict board passage using our model (PPV = 86%). Discussion: This study is the first validating the utility of milestones in a surgical specialty by demonstrating their ability to predict board passage. Residents with CREOGs or milestones below thresholds are at risk for board failure and may warrant early intervention.